The Correlation of Coping Strategies and Burnout Syndrome among Health Workers in Regional Hospital Dr. Soebandi Jember - Devi Octavia Kartika Sari; Ancah C N Marchianti; Inke Kusumastuti (Journal of Agromedicine and Medical Sciences, 2023)
The Covid-19 pandemic significantly impacts the mental health of health workers, including leading to the occurrence of burnout syndrome. Health workers in Dr. Soebandi Regional Hospital, as a regional referral hospital for Covid-19, were potentially exposed to the risk of experiencing burnout syndrome. Effective coping strategies might alleviate burnout syndrome symptoms. Therefore, this study was conducted to analyze the correlation of coping strategies and burnout syndrome level among health workers at Dr. Soebandi Regional Hospital. This cross-sectional study conducted from November to December 2021 included 88 physicians and nurses of Dr. Soebandi Regional Hospital. Data were collected using the Brief Cope Inventory and the Maslach Burnout Inventory Questionnaires. The SPSS spearman rho analysis showed a weak significant positive correlation of maladaptive coping strategies and burnout syndrome level (r=0.263; p=0.0013). The self-blame coping strategy had a weak significant positive correlation with burnout syndrome level (r=0.267; p=0.0012). We recommend to develop programs to protect health workers from becoming secondary victims of various adverse events and counseling provision to doctors and nurses regarding appropriate coping strategies for stress management at work. Keywords: Burnout Syndrome; coping strategy; RSD Dr. Soebandi; Mental Health.